1996
DOI: 10.1159/000276842
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vasoactive Intestinal Peptide, Substance P and Bombesin-Flanking Peptide in Nasal Polyps

Abstract: The presence of neuropeptide-containing sensory, parasympathetic and sympathetic nerves in human nasal mucosa is well established. However, information regarding the neuropeptide distribution in nasal polyps is still lacking. The aim of this study was to compare immunohistologically the presence and distribution of substance P (SP), vasoactive intestinal peptide (VIP) and bombesin-flanking peptide (BFP) in normal nasal mucosa and nasal polyps. The expression was studied using Formalin-fixed and paraffin-embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
4
2
Order By: Relevance
“… 21 The results of an immunohistochemical study by Kühn and Arnold indicated that substance P have an equal distribution in NPs and healthy nalas mucosa. 22 Our results, however, suggest higher level of substance P production in patients with NP than in subjects without nasal inflammation. We found no statistical difference between substance P levels in NANP and ANP, suggesting that this neuropeptide maybe has not a crucial role in the pathogenesis of “allergic” form of NPs.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“… 21 The results of an immunohistochemical study by Kühn and Arnold indicated that substance P have an equal distribution in NPs and healthy nalas mucosa. 22 Our results, however, suggest higher level of substance P production in patients with NP than in subjects without nasal inflammation. We found no statistical difference between substance P levels in NANP and ANP, suggesting that this neuropeptide maybe has not a crucial role in the pathogenesis of “allergic” form of NPs.…”
Section: Discussioncontrasting
confidence: 65%
“…As the main neuropeptide in the nasal mucosa, substance P has been reported to induce vasodilatation, vascular permeability and mucus secretion 21 . The results of an immunohistochemical study by Kühn and Arnold indicated that substance P have an equal distribution in NPs and healthy nalas mucosa 22 . Our results, however, suggest higher level of substance P production in patients with NP than in subjects without nasal inflammation.…”
Section: Discussioncontrasting
confidence: 49%
“…Elevated concentrations of substance P were found by Drake‐Lee et al ( 69); these findings were not confirmed in other publications ( 70).…”
Section: Other Mediatorsmentioning
confidence: 65%
“…However, neurogenic inflammation was demonstrated following capsaicin application to the nasal polyp tissue of non-allergic patients with nasal polyposis (12). The presence of neurokinins in the nasal polyps was established, but their role in pathogenesis remains unclear (17).…”
Section: Resultsmentioning
confidence: 99%